Tingkat Kecakapan Dalam Penggunaan Automasi Perpustakaan (Studi Kasus: Mahasiswa Prodi Perpustakaan dan Ilmu Informasi Angkatan 2020 Universitas Negeri Padang) - Putri, Tiara; Nabila, Jeihan (ARZUSIN, 2024)
The purpose of this study was to describe the level of digital skills of PII students class of 2020 UNP in using library automation. The type of research used is quantitative research with a descriptive approach. The population in this study were PII students of class 2020 UNP who had taken PKL using library automation, namely 57 people with nonprobability sampling. This study used the entire population as a sample. In this study, researchers used a questionnaire as an instrument. Data collection techniques were carried out by distributing questionnaires to all research samples, interviewing respondents as preliminary data, and literature studies. The results of this study indicate that: (1) the level of student skills (human/human) in using library automation has a total average score of 3.13 with a percentage of 78.25% in the high category, (2) the level of student skills (organisation) in using library automation has a total average score of 3.13 with a percentage of 78.25% in the high category. the use of library automation has a total average score of average total score of 3.15 with a percentage of 78.75% in the high category, (3) the level of student skills (technology/technology) in the use of library automation has a total average score of (3) the level of student skills (technology/technology) in using library automation has a total average score of 3.144 with a percentage of 78.6% in the high category, and (4) the level of student skills (user knowledge) in using library automation has a total average score of 3.384 with a percentage of 78.75% in the high category.